1999
DOI: 10.1034/j.1398-9995.1999.00200.x
|View full text |Cite
|
Sign up to set email alerts
|

A double‐blind, placebo‐controlled comparison of treatment with fluticasone propionate and levocabastine in patients with seasonal allergic rhinitis

Abstract: Fluticasone propionate aqueous nasal spray (FPANS) is a topically active glucocorticoid which has been successfully used for the treatment of seasonal allergic rhinitis (SAR). Topical levocabastine is a highly selective H1 antagonist which has been proposed as an alternative treatment of SAR. The purpose of this study was to compare the clinical efficacy of two topical nasal treatments, FPANS and levocabastine, in the treatment of SAR. Additionally, the effect of treatments on nasal inflammation was examined d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 20 publications
4
17
0
Order By: Relevance
“…The fourth study, Ortolani et al, 1999, investigated the efficacy and safety of FP nasal spray 200 mg once daily, levocabastine 200 mg twice daily, and placebo in 288 patients (aged 13-64 years) with SAR. Efficacy data from this study, as assessed via patient-recorded symptom scores (four-point scale), showed that the median percentage of days without eye symptoms in the FP 200 mg once daily treatment group was not statistically significantly different compared with placebo-treated patients (58.5 days vs. 56.1 days, respectively, p-value not reported) 47 .…”
Section: Fluticasone Propionatementioning
confidence: 98%
“…The fourth study, Ortolani et al, 1999, investigated the efficacy and safety of FP nasal spray 200 mg once daily, levocabastine 200 mg twice daily, and placebo in 288 patients (aged 13-64 years) with SAR. Efficacy data from this study, as assessed via patient-recorded symptom scores (four-point scale), showed that the median percentage of days without eye symptoms in the FP 200 mg once daily treatment group was not statistically significantly different compared with placebo-treated patients (58.5 days vs. 56.1 days, respectively, p-value not reported) 47 .…”
Section: Fluticasone Propionatementioning
confidence: 98%
“…12,13 The response to ASI was determined clinically by asking the patient the following: ''Do you feel better than you did before therapy?'' The answer could be one of the following:…”
Section: Vasmentioning
confidence: 99%
“…INS have been associated with reduced expression of histamine, a number of cytokines, and other inflammatory mediators produced and/or released by mast cells and basophils during the inflammatory cascade, as well as reduced expression of several proinflammatory cells involved in the pathogenesis of AR (lymphocytes, eosinophils, basophils, mast cells, Langerhans cells, and epithelial cells) (Table 3) [29,[34][35][36][37][38][39][40][41][42].…”
Section: Mechanism Of Action Of Intranasal Steroids In the Treatment mentioning
confidence: 98%